Pengaruh Kecanggihan Teknologi Informasi, PartisipasiManajemen, Dan Kemampuan Teknik Pemakai Sistem Informasi Akuntansi Terhadap Kinerja Individu(Studi Pada Skpd Kota Surakarta Yang Berada Di Balaikota Surakarta) - Rokhani, Nur; , Dr.Erma Setyawati, Ak.,MM (2017)
Individual performance affects the success of a company, the individual is expected to complete the task on time. So that individual performance goes well, an organization needs to consider the factors that have an influence on performance. The purpose of this study was to determine the influence of technological sophistication, the participation of agement, and engineering capabilities to the users of accounting information systems of individual performance. The research was conducted in SKPD of Surakata in Public hall of Surakarta . Number of samples taken were 70 respondents. Respondents in this study is the chairman and treasurer. This research uses non- probability sampling method, especially purposive sampling. Data was collected through interviews and questionnaires dokumentansi. The data analysis technique used is multiple linear regression. Results of this study indicate that kecangggihan information technology, management participation and technical capability users of accounting information system has a positive effect on individual performance.